HETEROSIS STUDIES FOR GRAIN YIELD AND ITS COMPONENTS IN WHEAT (TRITICUM AESTIVUM L. EM. THELL) UNDER NORMAL AND DROUGHT CONDITIONS - PANKAJ GARG,; R. P. SAHARAN,; MAMTA GUPTA,; RENU MUNJAL, (The Bioscan, 2015)
Heterosis for yield and its component traits were studied in 8 parents and their 28 F1s in wheat (Triticum aestivum L.) under normal and drought condition. Highest magnitude of heterobeltiosis was observed in cross PBW 343 x WH 1080 for effective tillers/plant (53.00%) followed by the cross PBW 343 x HD 2967 for grains/spike (49.27%) under normal environment, while under stress environment, crosses WH 1080 x HD 2967 for biomass/plant (60.61%) followed by the hybrid WH 730 x PBW 343 for grain yield (52.38%). For grain yield the crosses PBW 343 x WH 1080 and WH 730 x PBW 343 in normal environment and crosses WH 1080 x HD 2967 and WH 730 x PBW 343 were identified as promising on the basis of their high per se performance, average heterosis and heterobeltiosis. The manifestation of heterosis for effective tillers/plant, grains/spike and biomass/ plant seemed to be responsible for increased grain yield in these crosses. These crosses could be extensively used in breeding programme to develop superior segregants and or better pure lines could be derived in further breeding programmes.